The diversity and abundance of weeds in sugarcane (Saccharum officinarum) plantations and its relationships with Hymenoptera parasitoids diversity - DENNIS WIBOWO; BAMBANG TRI RAHARDJO; SRI KARINDAH; FAIZ NASIRUDDIN MUHAMMAD (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Wibowo D, Rahardjo BT, Karindah S, Muhammad FN. 2023. The diversity and abundance of weeds in sugarcane (Saccharum officinarum) plantations and its relationships with Hymenoptera parasitoids diversity. Biodiversitas 24: 2342-2349. Sugarcane (Saccharum officinarum L.) is an important plantation commodity in Indonesia. One of the strategies to improve sugarcane production is by controlling pest populations in sugarcane plantations which can be done by increasing the role of natural enemies as control agents, such as Hymenoptera parasitoids. The presence of parasitoids is influenced by the diversity of vegetation, including weed plants, due to the nectar contained in its flowers. The aim of this study was to investigate the diversity, abundance and composition of weeds in sugarcane plantations and their relationships with the diversity and abundance of Hymenoptera parasitoids that have the potential to control pests in sugarcane plantations. The study was conducted from June to August 2022 in four locations in East Java, i.e. Karangploso and Kalipare (Malang), Pasirian (Lumajang) and Gandusari (Blitar). Observation of weed vegetation was carried out by taking samples using 1 m x 1 m frame inside the observation point at each observation plot. Collection of Hymenoptera parasitoids used yellow pan trap and modified farmcop to determine the diversity of Hymenoptera parasitoids in the field. Observations were made at intervals of 1 week. We found that the highest abundance of weeds found across the four sugarcane plantations was Digitaria ciliaris (Retz.) Koeler, Ipomoea triloba L. and Ageratum conyzoides L. The highest abundance of Hymenoptera parasitoid species found were Trichogramma chilonis Ishii and Telenomus dignus Gahan. There were positive relationships between weed density and Hymenoptera parasitoid diversity and abundance at each sugarcane plantation. Weed species with the most presence of Hymenoptera parasitoids were A. conyzoides, I. triloba and Mimosa pudica L. In conclusion, the presence of weed vegetation on sugarcane plantations affected the composition of the Hymenoptera parasitoid community. The results of this study can be the rationale that the conservation of wild weeds in sugarcane fields is very important to support the existence of beneficial parasitoids.